Out-of-pocket expenditures of private households for dental services: Empirical evidence from Austria - Alice Sanwald; Engelbert Theurl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
Background: Dental services differ from other health services in several dimensions. One important difference is that a substantial share of costs of dental services ? especially those beyond routine dental treatment - are paid directly by the patient out-of-pocket. Objectives: We analyze the socio-economic determinants of out-of-pocket expenditures for dentals services (OOPE) in Austria on the household level. Methods: We use cross-sectional information on OOPE and on household characteristics provided by the Austrian household budget survey 2009/10. We apply a two-part model (Logit/GLM) and a one-part GLM. Results: The probability of OOPE is strongly affected by the life cycle (structure) of the household. It increases with adults? age, with income and partially with the level of education. The type of public insurance has an influence on the expenditure probability while the existence of private health insurance has no significant effect. In contrast to the highly statistically significant coefficients in the first stage the covariates of the second stage remain predominantly insignificant. According to our results, the level of expenditures is mainly driven by the level of education and income. The results of the one-part GLM confirm the results of the two-part model. Conclusions: Our results allow new insights into the determinants of OOPE for dental care. The household level turns out to be an adequate basis to study the determinants of OOPE, although we should be cautious to jump to conclusions for the individual level.
Keywords: I1; 330; out-of-pocket expenditures; dental services; two-part model; generalized linear model